Protocol for a randomised control trial of methylnaltrexone for the treatment of opioid-induced constipation and gastrointestinal stasis in intensive care patients (MOTION) - Patel,PB; Brett,SJ; O'Callaghan,D; Anjum,A; Cross,M; Warwick,J; Gordon,AC (BMJ Open, 2016)
Introduction: Gastro-intestinal dysmotility and constipation are common problems in intensive care patients. The majority of critical care patients are sedated with opioids to facilitate tolerance of endotracheal tubes and mechanical ventilation, which inhibit gastrointestinal motility and lead to adverse outcomes. Methylnaltrexone is a peripheral opioid antagonist that does not cross the blood-brain barrier and can reverse the peripheral side effects of opioids without affecting the desired central properties. This trial will investigate whether methylnaltrexone can reverse opioid induced constipation and gastro-intestinal dysmotility.Methods: This is a single centre, multi-site, double blind, randomised placebo controlled trial. Eighty-four patients will be recruited from four Intensive Care Units (ICU) within Imperial College Healthcare NHS Trust. Patients will receive intravenous methylnaltrexone or placebo on a daily basis if they are receiving opioid infusion to facilitate mechanical ventilation, and have not opened their bowels for 48 hours. All patients will receive standard laxatives as per the clinical ICU bowel protocol prior to randomisation. The primary outcome of the trial will be time to significant rescue-free laxation following randomisation. Secondary outcomes will include tolerance of enteral feed, gastric residual volumes, incidence of pneumonia, blood stream and Clostridium difficile infection, and any reversal of central opioid effects.Ethics and Dissemination: The trial protocol, the Patient / legal representative Information Sheets and Consent Forms have been reviewed and approved by the Harrow Research Ethics Committee (REC Reference 14/LO/2004). An independent Trial Steering Committee and Data Monitoring Committee are in place, with patient representation. Upon completion, the trial results will be published in peer-reviewed journals and presented at national and international scientific meetings.